THE FUNCTION OF IMAGERY IN CONTEMPORARY POETRY - Yuldasheva Mahinur Baxodir qizi; ABDURAMONOVA DIANA VALERYEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: One of the many strategies used by poets and other authors, whether intentionally or inadvertently, to strengthen their expressions is imagery. Therefore, it is essential that readers understand this literary device, but most readers do not take the use of imagery seriously or explain how it contributes to the successful literary analysis and teaching process. Poetry in particular benefits greatly from the use of "imagery," which stimulates the senses and helps readers understand the message that poets or other authors are trying to convey. Investigating the rationale behind the use of imagery and the degree to which it can further literary analysis and education is the primary concern  that  motivated  this  study.  Explaining  the  importance  of  images  in  literary analysis  and  the  teaching  process  is  the  study's  goal.  The  article's  references  were gathered from a variety of print and internet sources. To support the claim, a qualitative research approach based on secondary sources has been used. According to the study's findings, any text can become both formally and functionally appealing through the use  of  imagery.[1]  The  study  also  finds  that  by  stimulating  readers'  interest  and engaging  their  senses,  the  employment  of  imagery  in  literary  texts  improves  their perceptual capability.